(untitled) (Research, Society and Development, 2024)
Purpose: The purpose of this systematic review was to critically evaluate the existing literature and answer the question, “Which implant format and prosthetic platform promotes the least cervical resorption?”. Material and method: SCOPUS, PubMed/Medline, Web of Science, EMBASE, Lilacs, and Google Scholar databases were searched in September 2023. Results: The database search resulted in 2850 articles. Of the 12 articles selected for full reading, 2 remained in this systematic review. There is a lack of information to form an opinion and to perform statistical analysis of the data, so descriptive analysis was performed. Conclusions: Based on the studies included in this systematic review, the implant shape influences primary stability and osseointegration, but it is not yet possible to relate it directly to POC. However, the type of prosthetic platform has a direct influence. In addition to the type of prosthetic platform used, the various characteristics related to the shape of the implant must be considered to maintain satisfactory bone levels.